2018
DOI: 10.31327/jee.v3i1.477
|View full text |Cite
|
Sign up to set email alerts
|

The Use of E-Book to Improve Reading Comprehension Among Year 4 Pupils

Abstract: This is an Action Research of using the Story Jumper as an E-book to improve the reading comprehension among Year 4 pupils in one of the primary schools in Malaysia. The participants involved were twenty pupils consisting of seven males and thirteen females. Three data collection methods employed were pre-test and post-test, pupils’ work and teacher’s reflective journal. The findings showed that the use of E-book had increased the level of understanding in reading comprehension among the research participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…H2: Using information technology for e-book learning would affect learning effectiveness. Yee and Zainuddin (2018) identified a positive effect on the learning motivation and learning effectiveness of students. Elenein (2019) proposed that enhancing the learning motivation of students could significantly promote the learning effectiveness of students.…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…H2: Using information technology for e-book learning would affect learning effectiveness. Yee and Zainuddin (2018) identified a positive effect on the learning motivation and learning effectiveness of students. Elenein (2019) proposed that enhancing the learning motivation of students could significantly promote the learning effectiveness of students.…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…One of the non-printed teaching materials is the E-Book. According to previous study the implementation of interactive e-books can positively influence the level of interest exhibited by students (Bee Choo & Zainuddin, 2018). E-books assist and motivate students to improve their reading comprehension and performance to cultivate Zulherman / A Kvisoft Flipbook Maker-Assisted E-Book to Increase Students' Interest In Elementary Schools positive learning attitudes.…”
Section: Discussionmentioning
confidence: 94%
“…In the fourth article, according to Gilakjani (2012) in Yee & Zainuddin (2018) stated that the studies have shown that computer based multimedia can improve pupils' learning and retention of materials which are presented in class compared to study materials that do not incorporate the use of multimedia. From the implementation, the pupils had showed they could write more correct answers for reading comprehension in the worksheets.…”
Section: Discussionmentioning
confidence: 99%